Perkembangan, Kesiapan Dan Masalah Yang Dihadapi Oleh Lembaga Akreditasi Mandiri Kependidikan (LAMDIK) Sebagai Lembaga Akreditasi Mandiri - Khalilah Khalilah (Universitas Darunnajah Jakarta, Indonesia, 2022)
As imposed by National Acreditation Agency of Higher Education’s (BAN PT) regulation No.9, year 2020, Lembaga Akreditasi Mandiri Kependidikan (LAMDIK) is grated as a new accredication institution to acredidate the educational-related study programs. This article examines the degree to which did LAMDIK evolve and is being ready as an independent accreditation instution and what types of challenges it faces to do so. Having adopted the qualitative case study method, this article reveals that being facilitated by the Ministry of Education and Culture and BAN PT, two subsequent associations established LAMDIK in 2019s. They are association of educational scholars and association of the educational-related study programs. While striving to improve its institutional capacities, LAMDIK encountered the following issues, which are: total number of the existing educational-related study programs that should be facilitated by LAMDIK are too many (a), LAMDIK needs competent assessors that understood the characteristics of these educational-related study programs (b), most of LAMDIK’s assessors have no enough time and resources to facilitate accreditation processes of these educational-related study programs (c), which are located in diverse and romote area of this country (d) and not all of these educational-related study programs are really ready to be accredited by LAMDIK (e).